L’Oriente e l’Occidente visti da una principessa: Riflessioni su 'Memorie di una principessa etiope' di Martha Nasibù - Kornacka, Barbara Małgorzata (Incontri. Rivista europea di studi italiani, 2024)
The Orient and the Occident from the perspective of a princess. Reflections on Memorie di una principessa etiope by Martha NasibùThe paper analyses in what way the writer remembers her country and Italy, from the period of the Italian invasion of Ethiopia. Martha Nasibù being Ethiopian herself from an aristocratic family as well as having studied in Europe and in the USA, has her own and uncommon perspective. On the one hand, in her novel she deconstructs the historical hierarchy of the Occident (superior) and the Orient (inferior), because the Ethiopians are cultured, noble and superior and the Occidentals, the Italians, in contrast are often represented as rude, violent and insensible. On the other hand, her perspective is limited by her location and lacks an intersectional gaze.